Influência da utilização do incentivo financeiro do PMAQ na qualificação da atenção básica dos municípios da Paraíba sob o ponto de vista dos gestores municipais - Lago, Vivian Conceição Alves Leite Pereira do (2022)
According to the Ministry of Health, the National Program for Improving Access and Quality of Primary Care (PMAQ-AB) wasestablished in 2011 withthe objective of encouraging managers and teams to improve the quality of health services. In view of the a bove, the objective of this study was to analyze the perception of Primary Care (AB) managers about the transfer of the financial incentive of the National Program for the Improvement of Access and Quality (PMAQ), and its application to obtain quality in primary care, in the municipal it ies of Paraíba. This is a cross-sectional research base donan epidemiological study, in which the fator and effect are observed in the same historical moment. The study is anexcerpt from anotherre search entitled 'Impacts of the PMAQ-AB on Primary Care: Analysis of the application of the financial incentive for performance to health teams in Brazil'. The research data base was built by researchers from the Research Groupon Policy, Educationand Health Care – GPECS at UFPB, basedon a questionnaire Applied to managers of Primary Care in the Municipal ities of the State of Paraíba. This is a cross-sectional study with a quantitative approach. The variables and the ir concepts will be inserted in the SPSS software, version IBM® SPSS Statistics, Where the data will be app reciated, emphasizing the importance of ad justing the variables, in order to be tteranalyze the epilogues, as logistic regression will be worked, basedon a model binary. Theresults show that most of the financial incentive received by the municipal it yisused in the transfer to primary care health teams, as well as in the structural part of the UBS. Among the measures applied to carry out the transfer, the adoption of the use of external evaluation as a method for the transfers tood out; the percentagem value Applied to the Monthly remuneration of each professional; the percentagem be tween 40% and 60% of the amountsgranted to workerson a biannualbasis, alsohighlighti ngth at therest of there sources are invested in better working conditions; adjust ments to the UBS structure; permanente education, amongothers. Thus, wecon clude that the use of the pay-for-performance strategy requires managers to be a ble to motivate workers to a great ercommitmen tto wards qualification in ABS. However, in general, workers are concerne dabout receiving the transfer of resources from the PMAQ as an incentive for their performance, while managers are more concerne dabout usingre sources to purchase medicines and supplies.